Surface morphology study on aluminum alloy after treated with silicate-based corrosion inhibitor from paddy residue - Mohamad, N.; Jalar, A.; Othman, N.K. (Universiti Kebangsaan Malaysia, 2014)
Aluminum alloys have extensive applications in engineering structures like aircraft due to their high strength-to-weight ratio. However, these alloys are very reactive and prone to corrosion attack. Paddy waste is one of the beneficial natural sources that have a potential contribution on inhibiting the corrosion attack. At 600°C, silica was obtained from rice husk ash. The chemical reaction between silica powders with concentrated alkali generates formulation of potential silicate-based corrosion inhibitor. The potentiodynamic polarization, optical microscope (OM), infinite focus microscope (IFM) and scanning electron microscopy (SEM) were employed to investigate the corrosion behaviour of Al 6061 through electrochemical and surface study. The electrochemical measurement showed that the existence of silicate-based corrosion inhibitor in 0.5 M hydrochloric acid medium significantly mitigates the corrosion rates. SEM, IFM and OM showed that the morphology of untreated Al 6061 contributes more damage on the sample surface than that of Al 6061 treated with silicate-base corrosion inhibitor. The aim of this study was to attain better understanding of surface study on corrosion behaviour of aluminum alloy in acidic medium after treated and untreated with silicate-based corrosion inhibitor from paddy residue.